Penerapan Standar Akuntansi Syariah Pada Laporan Keuangan Koperasi Simpan Pinjam Mandiri Di Kabupaten Luwu - Rifqiansyah . (CV. ITTC INDONESIA, 2026)
Background: The quantity and completeness of Islamic Financial Institutions in Indonesia continue to increase, indicating that the Islamic financial sector in this country is now developing very rapidly, especially in Islamic Microfinance Institutions (LKMS). This prompted the Minister of State for Cooperatives and Small and Medium Enterprises (KSPPS) to issue a Ministerial Decree concerning the Implementation of Islamic Savings and Loans Business Activities by Cooperatives. The purpose of this study is to determine whether the financial statements of the Mandiri Savings and Loans Cooperative in Luwu Regency comply with Islamic accounting rules. Interviews and documentation are the basis of this descriptive qualitative research approach. Interview and documentation methods are used to collect data. Qualitative descriptive analysis methods are used to examine the collected data. Based on the results of the study, the Mandiri Savings and Loans Cooperative in Luwu Regency has not prepared and presented financial statements in accordance with Islamic accounting rules. This is evident from the way the murabahah contract is used in the presentation and disclosure of financial statements. The financial condition report does not comply with PSAK 101 because the temporary joint fund is included in the liabilities on the balance sheet of the Mandiri Savings and Loans Cooperative, which should be shown separately from liabilities. In contrast, the financial accountability of the Mandiri Savings and Loans Cooperative only consists of a cash flow statement, balance sheet, and calculation of operating results (profit/loss). This contradicts PSAK 101, which requires reporting on charitable funds, sources and uses of zakat, and notes to the financial statements. Murabahah and mudharabah transactions are also subject to PSAK 102 and 105. Even in cases where both transactions have been agreed upon, the study concludes: Several members of the Luwu Regency Savings and Loans Cooperative who apply PSAK 101, 102, and 107 indicate the use of murabahah contracts or agreements.